2017
DOI: 10.1128/jvi.00066-17
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Dose Recombinant Parainfluenza Virus 5-Vectored Vaccine Expressing Respiratory Syncytial Virus (RSV) F or G Protein Protected Cotton Rats and African Green Monkeys from RSV Challenge

Abstract: Human respiratory syncytial virus (RSV) is a common cause of severe respiratory disease among infants, immunocompromised individuals, and the elderly. No licensed vaccine is currently available. In this study, we evaluated two parainfluenza virus 5 (PIV5)-vectored vaccines expressing RSV F (PIV5/F) or G (PIV5/G) protein in the cotton rat and African green monkey models for their replication, immunogenicity, and efficacy of protection against RSV challenge. Following a single intranasal inoculation, both animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 55 publications
3
33
1
Order By: Relevance
“…Perhaps virus transmission from camels to humans can be blocked, with concomitant immunization of high-risk human populations, as proposed by CEPI (The Coalition for Epidemic Preparedness Innovations) and WHO. As a vaccine vector, PIV5 has been effective in mice, cotton rats, hamsters, guinea pigs, ferrets, dogs, and nonhuman primates (25,(46)(47)(48)(49). It will be worthwhile to test PIV5-MERS-S in camels in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps virus transmission from camels to humans can be blocked, with concomitant immunization of high-risk human populations, as proposed by CEPI (The Coalition for Epidemic Preparedness Innovations) and WHO. As a vaccine vector, PIV5 has been effective in mice, cotton rats, hamsters, guinea pigs, ferrets, dogs, and nonhuman primates (25,(46)(47)(48)(49). It will be worthwhile to test PIV5-MERS-S in camels in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This work demonstrated that a single‐dose immunization with PIV5/F or PIV5/G elicited protective immunity against RSV challenge in mice. PIV5/F and PIV5/G were further evaluated as single‐dose inoculations in more relevant preclinical animal models . In cotton rats, both PIV5/F and PIV5/G elicited RSV‐specific serum antibodies and conferred complete protection in the lung against RSV challenge.…”
Section: Piv5‐vectored Vaccines Against Human and Animal Infectious Dmentioning
confidence: 99%
“…Parainfluenza virus (PIV) is the second most common cause of respiratory tract infection hospitalization in children. Two PIV5 chimeras expressing RSV F or RSV G protein were used to inoculate cotton rats and African green monkeys [23]. Although both chimeras fully protected naive animals from RSV infection, the RSV F protein chimera (PIV5/F) stimulated a higher antibody titer in African Green monkeys than RSV G protein (PIV5/G) [23].…”
Section: Chimeric Vaccinesmentioning
confidence: 99%
“…Two PIV5 chimeras expressing RSV F or RSV G protein were used to inoculate cotton rats and African green monkeys [23]. Although both chimeras fully protected naive animals from RSV infection, the RSV F protein chimera (PIV5/F) stimulated a higher antibody titer in African Green monkeys than RSV G protein (PIV5/G) [23]. Also, they both boosted antibody levels in RSV pre-exposed African Green monkeys, suggesting that the PIV5/F vaccine could be helpful to naïve babies and pre-exposed elderly people [23].…”
Section: Chimeric Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation